Liquidity Constraints: A Cross-Section Analysis of the Housing Purchase Behavior of Japanese Households - Maki, Atsushi (The Review of Economics and Statistics, 1993)
This paper focuses on the existence of liquidity constraints on housing purchases by Japanese households. In order to assess the impact of liquidity constraints, the author analyzes the housing purchase behavior of worker households which rent and in which the household head was under the age of forty-five from the National Survey of Family Income and Expenditure compiled by the Statistics Bureau. Liquidity constraints emerge as the most important factor in determining housing purchase behavior. Copyright 1993 by MIT Press.